Two independent real-time precursors of the 7.8 Mw earthquake in Ecuador based on radioactive and geodetic processes—Powerful tools for an early warning system. (May 2019) - Toulkeridis, Theofilos; Porras, Luis; Tierra, Alfonso; Toulkeridis-Estrella, Katerina; Cisneros, David; Luna, Marco; Carrión, Jose Luis; Herrera, Myrian; Murillo, Alfonso; Perez Salinas, Juan Carlos; Tapia, Santiago; Fuertes, Walter; et al.
Abstract: The 7.8 Mw earthquake in Ecuador during spring of 2016 was an unprecedented opportunity to collect data on two independent seismic precursors. The first precursor was based on the radiation of the environment, which changed considerably several hours before the main earthquake. Real-time data was collected by measurements at every minute. However, these determinations occurred before and after the main earthquake of 2016, and any significant seismic event of >5.0 Mw, was recorded with an increase of hundreds to becs/min several hours before such telluric movements. Seismic events of less than or equal to 5.0 Mw were also possibly recorded, if the events were close to the surface. The second seismic precursor was set up thanks to 24 GPS stations spread all over the Ecuadorian continent, which registered several minutes before the main earthquake a significant change in their usual position. These measurements allow the exact position of every station to send a signal to the main base every second. Such significant alteration of the main point was determined exclusively for the main 7.8 Mw earthquake, while other, less intense seismic activities were not recorded at all. Based on our measurements in real-time, we can conclude that the two precursors, independent from each other, are powerful tools for the implementation of an early warning system of earthquakes for forecasting in the medium and short term in active continental margins.